Exploring the Ocular Transmission Potential of Severe Acute Respiratory Syndrome Coronavirus 2 and the Assessment of Conjunctival Swab Test Results: A Concise Review - Arash Mirzaei; Ali Djalilian; Seyed Mahbod Baharnoori; Bahram Bohrani Sefidan; Mansoor Shahriari; Kasra Cheraqpour; Mahmood Ghassemi; Allison Kufta; Mohammad Soleimani (Journal of Current Ophthalmology)
Purpose: To evaluate the possibility of coronavirus disease 2019 (COVID-19) transmission through the eyes, particularly through the ocular surface and conjunctival route, as well as the positivity of conjunctival swab test. Methods: A narrative review was conducted to assess the possibility of COVID-19 transmission and the role of conjunctival swabs in diagnosing COVID-19 patients. Several studies were analyzed to compare the positivity rates and sensitivities of conjunctival swabs versus nasopharyngeal swabs. Results: Despite the fact that respiratory droplets are the major route of severe acute respiratory syndrome coronavirus 2 transmission, the eyes can potentially serve as an active (via tears) or passive route (via the nasolacrimal duct) of infection. Besides, conjunctival swabs exhibited a low positive rate and sensitivity for detecting COVID-19 compared to nasopharyngeal swabs. While nasopharyngeal swabs typically showed positivity rates between 60% and 100%, conjunctival swabs ranged from showing no detectable evidence to a 57% positivity rate. Conclusions: Despite the low transmission rate through the eyes, thorough consideration is necessary as ocular transmission cannot be entirely ruled out. Further research and vigilance are warranted to better understand and mitigate potential ocular routes of COVID-19 transmission.